Preparation and kinetic study of organic amine‐loaded ion‐exchange resin as CO2 adsorbents. Issue 1 (15th July 2020) - Liu, Xinmin; Qiu, Xuexia; Sun, Xin; Mei, Libin; Wang, Lingyun; Guo, Qingjie
Abstract: Organic amine adsorbents prepared by template method using ion exchange resin (D001) as support and polyethyleneimine (PEI) as a modifier, and the preparation process was optimized by orthogonal experiment plan. The results showed that adsorbents prepared under conditions (the copper ion concentration was 0.2 mol/L, the ultrasonic time was 3 hr, and the PEI loadings were 30%) had an excellent CO2 adsorption properties. The effects of temperature and gas influent velocity on CO2 adsorption properties were investigated in a fixed bed reactor. When PEI loadings were 30%, the adsorption temperature was 65°C and the gas influent velocity was 40 ml/min, organic amine adsorbents performed a better PEI dispersion, stability, and CO2 adsorption capacity. Maximum CO2 adsorption capacity was 4.00 mmol/g. Besides, the CO2 adsorption capacity decreased by only 10% after 10 cycles of adsorption–desorption tests, attribute to a small amount of PEI was volatilize during the regeneration process. The external diffusion was eliminated by increasing the gas influent velocity, and the adsorption data were well fitted the Weber‐Morris particle diffusion model, indicating that CO2 adsorption was controlled by internal diffusion.